Electrode processes in electrolysis of zirconium at production of plastic zirconium for nuclear energy - Mukhachev, A.P.; Nefedov, V.G.; Kharytonova, O.A. (Вопросы атомной науки и техники, 2019)
The analysis of the conditions for industrial production of zirconium by the electrolysis of a melt of potassium fluorozirconate and potassium chloride in a sealed electrolyzer with a current load of 10 kA was carried out. It is shown that the developed method of preparing the raw material without the use of chlorine, with electrolytic reduction of zirconium provides the production of a metal of nuclear purity, with a hafnium content of less than 0.005 wt.% polyvalent ion electrodes. The current output of zirconium is 55...60%, which may be due to reversible oxidation-reduction on the electrodes of polyvalent ions. The low resistance of the graphite anode is due to both chemical interaction with the released fluorine and chlorine, and its mechanical destruction.